2021
DOI: 10.1007/s00520-021-06495-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of netupitant/palonosetron combination (NEPA) in preventing nausea and vomiting in non-Hodgkin’s lymphoma patients undergoing to chemomobilization before autologous stem cell transplantation

Abstract: Purpose Prevention of chemotherapy-induced nausea and vomiting (CINV) is particularly challenging for patients receiving highly emetogenic preparative regimens before autologous stem cell transplantation (ASCT) due to the daily and continuous emetogenic stimulus of the multiple day chemotherapy. While studies have shown effective prevention of CINV during the conditioning phase with NK1 receptor antagonist (NK1RA)-containing regimens, there have been no studies evaluating antiemetic use during ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…A subgroup analysis revealed that men in the NK1RA group had improved CR, while women had similar CR in both the NK1RA and without NK1RA groups. Overall, these data add to the growing body of evidence describing the unmet clinical need for adults with hematologic malignancies receiving multiday chemotherapy and experiencing CINV [3,4,[14][15][16].…”
Section: Discussionmentioning
confidence: 89%
“…A subgroup analysis revealed that men in the NK1RA group had improved CR, while women had similar CR in both the NK1RA and without NK1RA groups. Overall, these data add to the growing body of evidence describing the unmet clinical need for adults with hematologic malignancies receiving multiday chemotherapy and experiencing CINV [3,4,[14][15][16].…”
Section: Discussionmentioning
confidence: 89%
“…The updated guidelines from the American Society of Clinical Oncology (2020) and the National Cancer Comprehensive Network (2017) included olanzapine to triple therapy as prophylaxis to CINV in high emetic risk chemotherapy, but did not address HCT in these updates. In addition, HCT patients are a heavily pre-treated and immunocompromised subgroup of patients, and some data shows the exploration of decreasing/eliminating the use of corticosteroids in these patients due to acute and chronic adverse events [ 2 , 3 ].…”
Section: Resultsmentioning
confidence: 99%
“…Response rates were 77.8% for complete response (no emesis and no rescue use), 72.8% for complete control (complete response and no more than mild nausea), 86.4% for no emesis, and 82.7% for no rescue use during the overall phase (duration of chemo-mobilization through 48 h after). These phase IIa results suggest that NEPA may make it possible to eliminate corticosteroids in these heavily pretreated and immunocompromised patients [ 2 ].…”
Section: Resultsmentioning
confidence: 99%